2021
DOI: 10.1186/s12870-021-03297-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic responses to drought stress in Polygonatum kingianum tuber

Abstract: Background Polygonatum kingianum Coll. et Hemsl. is an important plant in Traditional Chinese Medicine. The extracts from its tubers are rich in polysaccharides and other metabolites such as saponins. It is a well-known concept that growing medicinal plants in semi-arid (or drought stress) increases their natural compounds concentrations. This study was conducted to explore the morpho-physiological responses of P. kingianum plants and transcriptomic signatures of P. kingianum tubers exposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 107 publications
(82 reference statements)
1
5
0
Order By: Relevance
“…These DEGs exhibited significant enrichments for molecular functions GO terms related to cytoskeleton, hydrolase activity, cellular redox, and binding; biological processes terms involving the cell or subcellular processes; and cellular component terms concerned with membrane function and photosynthesis. These findings are in agreement with other studies [ 30 , 31 , 32 , 33 , 34 , 35 ] and suggest that the genes associated with these GO terms might be involved in drought tolerance. Notably, DEGs relating to photosynthesis, including genes involved in the photosystem, photosynthetic membrane, photosystem II, photosynthesis, photosystem I reaction center, photosystem II oxygen evolving complex, and photosystem I, were typically down-regulated under drought stress, indicating that photosynthetic functions were inhibited (especially from 5 d on).…”
Section: Discussionsupporting
confidence: 93%
“…These DEGs exhibited significant enrichments for molecular functions GO terms related to cytoskeleton, hydrolase activity, cellular redox, and binding; biological processes terms involving the cell or subcellular processes; and cellular component terms concerned with membrane function and photosynthesis. These findings are in agreement with other studies [ 30 , 31 , 32 , 33 , 34 , 35 ] and suggest that the genes associated with these GO terms might be involved in drought tolerance. Notably, DEGs relating to photosynthesis, including genes involved in the photosystem, photosynthetic membrane, photosystem II, photosynthesis, photosystem I reaction center, photosystem II oxygen evolving complex, and photosystem I, were typically down-regulated under drought stress, indicating that photosynthetic functions were inhibited (especially from 5 d on).…”
Section: Discussionsupporting
confidence: 93%
“…Plant-pathogen interactions, which exhibit two patterns, PAMP-triggered immunity (PTI) and effector-triggered immunity (ETI), are crucial physiological processes that occur in plants [ 43 ]. It has been reported that drought stress could trigger the plant-pathogen interaction and regulate the expression of genes implicated in this pathway, such as FLS2, CNGCs and SGT1 [ 44 ]. FLS2 (flagellin sensitive 2), which exists in the plasma membrane, is one of the immune signal receptors participating in the plant-pathogen interaction pathway and can cause a decline in ROS [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Song et al. (2021) found that japonica and indica rice exhibit strongly DEGs related to the glutathione metabolic pathway under water shortage conditions, while Qian et al. (2021) found that the expression of DEGs related to starch and sucrose metabolic pathways was increased under drought conditions, indicating their importance in stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Kumar et al (2020) found that DEGs related to plant hormone signal transduction are regulated under drought stress in mung beans, while Yu et al (2020) found that DEGs related to phenylpropanoid biosynthesis have important regulatory roles under drought stress in foxtail millet. Furthermore, Song et al (2021) found that japonica and indica rice exhibit strongly DEGs related to the glutathione metabolic pathway under water shortage conditions, while Qian et al (2021) found that the expression of DEGs related to starch and sucrose metabolic pathways was increased under drought conditions, indicating their importance in stress tolerance. These findings, together with those of this study, confirm that "plant hormone signal transduction", "phenylpropane biosynthesis", "glutathione metabolism", and "starch and sucrose metabolism" are important pathways in maize responses to drought stress, which further supports the findings of the current study.…”
Section: Mirna Sequencing Analysis and Drought Stress Responsementioning
confidence: 99%